Electrochemistry-assisted surface plasmon resonance detection of miRNA-145 at femtomolar level - Ribeiro, José A. (2021)
In this work, we combined electrochemical techniques with SPR (eSPR) for the label-free detection of cancer biomarker miRNA-145. Detection was performed in a simple two-step assay. In the first step, the gold sensor surface, previously functionalized with a self-assembled monolayer (SAM) of thiolated RNA probes is incubated with the sample containing the target RNA biomarker. In this step, hybridization of RNA fragments with complementary immobilized probes was monitored in real-time by SPR. In the second step, eSPR measurements were performed to improve the sensitivity of the hybridization assay. Potential-induced deposition of a redox probe at the sensor surface resulted in enhanced SPR response promoted by the electrochemical process, thereby allowing the detection of miRNA-145 at femtomolar level (LOD = 0.56 fM), without sample derivatization or post-hybridization treatment for signal amplification. Good linearity was achieved (R2 = 0.984) over the concentration range from 1.0 fM and 10 nM. Furthermore, the developed eSPR biosensor showed high selectivity towards single-base and two-base mismatch sequences and detection of target miRNA-145 in synthetic human serum was successful achieved.